The relationship between father involvement and children’s academic achievement: a systematic review - He Yanjie; Latha Ravindran; Luo Limei (Institute of Advanced Engineering and Science, 2026)
Father involvement in children’s education and its impact on children’s academic achievement has become a pertinent topic. However, there has not been a systematic assessment of the mechanisms and factors that specifically influence the impact of father involvement on children’s academic achievement. To this end, this study reviewed studies published between 2014 and 2024 and identified and analyzed 45 articles from databases such as Web of Science, Scopus, ERIC, and Google Scholar using a two-stage review protocol of automated literature search and manual screening. It was found that the multidimensionality of father involvement has a significant effect on children’s academic achievement and that this relationship is influenced by a combination of individual father factors, family factors, school factors, and socio-cultural factors. Based on the limitations of existing studies, this study constructed a structured empirical research framework to categorize the influencing factors and made recommendations for future research, including conducting longitudinal studies, considering different socio-demographic variables, conducting cross-cultural comparative studies, and exploring in depth the potential mechanisms underlying the association between father involvement and children’s academic achievement, with the aim of providing stronger support and guidance to promote fathers’ active participation in their children’s education and better promote children’s holistic development.